EVALUATION OF THE HEMATOLOGY TEST IN THE DIAGNOSIS OF CANINE EHRLICHIOSIS - Hoyos S., Luis (2007)
The present study evaluated the level of agreement between the hematology test and the direct ELISA assay for the diagnosis of canine ehrlichiosis. It was used 77 samples from dogs with clinical signs compatible with canine ehrlichiosis and 20 control samples from the Hospital of Small Animals of the Veterinary Medicine Faculty, San Marcos National University. The results showed 84.7 ± 11.0% of concordance by the Kappa test. Likewise, the thrombocytopenia, leukopenia, anemia and history of tick infestation were significantly related (p<0.05) to clinical evidence of the disease. The results revealed that the hematology test was important in the diagnosis of canine ehrlichiosis and that the direct ELISA was an excellent confirmatory test.